Online Teaching and Learning: Experiences of Teachers and Students during the COVID-19 Pandemic in Kathmandu - Gyawali, Sindhu (MVIC Journal of Management and Information Technology, 2025)
The unprecedented COVID-19 pandemic has created havoc in the human world and affected every part of human life. The sudden outbreak of COVID-19 immensely affected the education sector. Governments everywhere imposed lockdown restrictions such as COVID-19 demanded social distancing and isolation measures. Against this backdrop, colleges, universities, and schools in Nepal have switched to online mediums from face-to-face classes so that the education sector won’t be disrupted. Online learning is in the nascent stage in countries like Nepal. This study explored the teacher-student experiences of the sudden transition to online learning during the COVID-19 pandemic in higher education. The researcher has combined the use of questionnaires and interviews to gather data on challenges teachers and students face in online teaching experience and their experiences of the use of the online approach. At first stage, the survey was conducted with a pre-structured questionnaire, then the in-depth interview was assessed with faculties and students who were engaged in online classes during the pandemic period. The research revealed teachers’ and students’ preferences for face-to-face learning over online learning which also reflects post -covid scenario and suggests the return to physical classrooms after COVID-19.